Role of lasers as an adjunct to scaling and root planing in patients with type 2 diabetes mellitus: a systematic review - Abduljabbar, T.; Javed, F.; Shah, A.; Samer, M.S.; Vohra, F.; Akram, Z. (Springer Verlag, 2017)
The aim of the study was to assess the efficacy of adjunctive use of laser therapy (LT) alone or antimicrobial photodynamic therapy (aPDT) to improve clinical periodontal and HbA1c levels in patients with both chronic periodontitis (CP) and type 2 diabetes mellitus (T2DM). Electronic search of the MEDLINE, PubMed, EMBASE, Science Direct, and SCOPUS databases were combined with hand searching of articles published from 1975 up to and including March 2016 using relevant MeSH terms. Six studies were selected for this review. In these six studies, laser treatment was applied, after scaling and root planing (SRP), in two ways: Three studies used laser alone and three studies used laser with photosensitizer. All the six included studies reporting clinical periodontal and glycemic parameters showed that LT and aPDT were effective in the treatment of CP in T2DM subjects at follow-up. Two studies showed significantly better periodontal outcomes for LT as an adjunct to SRP as compared to SRP alone, whereas four studies showed comparable periodontal outcomes among adjunctive LT or aPDT with SRP. Two studies showed significant reduction of HbA1c levels in LT and aPDT as compared to SRP, whereas three studies showed comparable percentage levels at follow-up. It remains debatable whether LT or aPDT as adjunct to SRP is more effective as compared to SRP alone in the improvement of clinical periodontal and glycemic control in patients with both CP and T2DM, given that the scientific evidence is weak.